Novel Ferrocenyl Methyl Î²-Diketone Complexes with Potent Antimicrobial Properties and Cytotoxicity (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Ferrocenyl complexes; Antimicrobial activities; Cytotoxic properties Bangladesh j. genet. biotechnol. 7(1&2): 65-702006 (June & December)